Using Gamification to Improve the Quality of Educating Children with Autism - Afrasiabi Navan, Azadeh; Khaleghi, Ali (Revista Científica, 2020)
This study was conducted with a pre-test–post-test design with a control group in which participants were divided into two experimental (ten persons) and control (ten persons) groups. The Smile 1 intervention took place in 16 sessions of 30 min, which consisted of eight sessions of 1 h owing to the time spent by the parents of the participants in the study. Additionally, a Child Behaviour Check List (CBCL) was used to measure the effectiveness of this interventional game on reducing the behavioural problems of children that participated. The questionnaire consists of 113 questions in which 13 different behavioural factors are identified in the children. For this purpose, pre-test and post-test stages were performed for both groups. In fact, due to time constraints for holding intervention sessions, it was expected from the outset that significant changes in participant behaviour during the two months of interventions would not be observed.